1997
DOI: 10.1002/(sici)1097-4660(199711)70:3<299::aid-jctb757>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phenol biodegradation by south magnetic field exposure

Abstract: : Microbial pellets in the presence of south pole magnetic Ðelds demonstrate enhanced oxidation of phenol. Earlier work at 0É49 tesla indicates qualitatively that a unipolar north magnetic Ðeld inhibits and a south magnetic Ðeld accelerates phenol oxidation rates of an alginate immobilized, mixed bacterial culture bioreactor. This work demonstrates further enhancement by exposure during phenol oxidation at 0É15 and 0É35 tesla, as well as by exposure during acclimation of the free microorganisms prior to immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…However, SMF affects the synthesis of HSPs in E. coli but in a manner that it depends on the signal characteristics [55]. The findings in this particular study is consistent with some other researchers reports especially with respect to biological models exposed for short duration of 30 to 60 min and at 50/60 Hz SMF exposure of low magnetic flux density (8-2300 µT) [97][98][99][100]. In terms of SMF effect on the changes in gene transcription, some works have been reported.…”
Section: Effect Of Static Magnetic Field On Enzyme Activity Gene Trasupporting
confidence: 89%
“…However, SMF affects the synthesis of HSPs in E. coli but in a manner that it depends on the signal characteristics [55]. The findings in this particular study is consistent with some other researchers reports especially with respect to biological models exposed for short duration of 30 to 60 min and at 50/60 Hz SMF exposure of low magnetic flux density (8-2300 µT) [97][98][99][100]. In terms of SMF effect on the changes in gene transcription, some works have been reported.…”
Section: Effect Of Static Magnetic Field On Enzyme Activity Gene Trasupporting
confidence: 89%
“…Another study (Yavus and Celebi, 2000) has demonstrated that the organic substrate removal rate was first increased by increasing the magnetic field strength, and reached the maximum at 17.8 mT, but then decreased with further increase of magnetic field. Previous work also (Jung and Sofer, 1997) demonstrates further enhancement of phenol oxidation activity under the exposure of magnetic field at 0.15 and 0.35 T was possible.…”
Section: Introductionmentioning
confidence: 81%
“…Studies have demonstrated that using MW for irrigation can improve water productivity. In addition, MW is reportedly effective at preventing and removing scale deposits in pipes and water containing structures [9,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Magnetic Water Treatment In Agriculturementioning
confidence: 99%
“…The MF induction reported by previous studies is wide and ranges 7 to 490 mT [17,30,38,39,47]. Jung and Sofer [38] showed that application of MF at induction of 150 and 350 mT improved phenol biodegradation through immobilized activated sludge. They used unipolar South Pole of MF.…”
Section: Technical Considerations and Mechanism Of Actionmentioning
confidence: 99%